2018
DOI: 10.1007/s12011-018-1315-0
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Minerals in Nectar Honeys from Direct Sale and Retail in Poland

Abstract: The aim of the study was to compare the content of selected minerals in different nectar honeys (acacia, buckwheat, raspberry, linden, rapeseed, and multifloral) available on the Polish market. The degree to which the demand for eight minerals (K, Na, Mg, Ca, Zn, Fe, Mn, Cu) by adults is met by a portion of 100 g of honey was estimated as well. The material consisted of 34 artisanal honeys from direct sale and 34 samples purchased from retail stores. The artisanal honeys contained significantly more K, Mg, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Multivariate analysis (e.g., principal component analysis-PCA; hierarchical cluster analysis-HCA; linear discriminate analysis-LDA, and others) has very often been used to evaluate and/or classify honeys in terms of their chemical composition or their physicochemical or biological properties. Numerous papers have confirmed the suitability of this method for honey, used either alone [ 10 , 11 , 12 , 13 , 14 ] or in combination with spectroscopic techniques [ 15 ].…”
Section: Introductionmentioning
confidence: 97%
“…Multivariate analysis (e.g., principal component analysis-PCA; hierarchical cluster analysis-HCA; linear discriminate analysis-LDA, and others) has very often been used to evaluate and/or classify honeys in terms of their chemical composition or their physicochemical or biological properties. Numerous papers have confirmed the suitability of this method for honey, used either alone [ 10 , 11 , 12 , 13 , 14 ] or in combination with spectroscopic techniques [ 15 ].…”
Section: Introductionmentioning
confidence: 97%
“…The first observation that darker honeys had a higher mineral content than light honeys was made by Anklam in 1998 [79]. Subsequent correlative studies revealed significantly higher quantities of transition metal ions Fe, Zn, Cu, and Mn in buckwheat, heather, and honeydew in comparison to light honeys such as acacia or rape honey [74,[80][81][82].…”
Section: Presence Of Transition Metalsmentioning
confidence: 99%
“…The concentrations displayed in our study are much higher than that found in other local and foreign honeys. 44 The critical aspect of this analysis is based on both the composition of the soil and the floral diversity.…”
Section: Papermentioning
confidence: 99%